Hubungan Keselamatan dan Kesehatan (K3) dengan Produktivitas Kerja Karyawan (Studi Kasus: Bagian Pengolahan PTPN VIII Gunung Mas, Bogor) - Lestari, T.; Trisyulianti, Erlin (Jurnal Manajemen, 2009)
Competitiveness business need high quality human resources. Human resources as workforce in the industry must be protected by Health and Safety programme (K3). This reseach apropiate five factors K3, ie: safety training, safety work publication, environment work, monitoring and disiplin, and improving awareness K3. Productivity can see from productivity factors ie motive work, ability, enviroment, compensasion, social garancy, and work relationship. The objective of this research is to analyze between the health and safety programme and work productivity. This research uses survey, sampling method and questioners as the tools in collecting the main data. This research is conducted in Production division PTPN VIII Gunung Mas, Bogor. To analyze data uses descriptive analyzis and correlation analyzis. Rank Spearman is used to analyze the correlation. This research shows these following results: there is significant correlation and positive between the health and safety programme and work productivity. Keywords: Health and Safety Programme, Work Productivity.